Pengaruh Struktur Modal, Profitabilitas, Ukuran Perusahaan Dan Likuiditas Terhadap Nilai Perusahaan(Studi Pada Perusahaan Keuangan Non Perbankan Yang Terdaftar Di Bei Tahun2010-2014) - Pardiyanto, Pardiyanto, Dr. Erma Setiawati, Ak, MM (2016)
There are so many companies in Indonesia which have sold their stocks to go public. These companies operate in any sector, but the most interesting to be researched is company or organization which operates in finance sector. The finance company is divided into banking company and non banking company or financial organization non bank. This study aimed at testing the effect of capital structure, profitability, company size and liquidity of company value. The polulation of this study was all the non banking financial company which was registered in Indonesian Stock Exchange in 2010-2014. The sample in this study was chosen with purposive sampling method. There were 31 sample. In this study, the testing data used clasic assumtion test, double regression, T-test and F-test. The result showed that capital structure variable which was measured with DER had no effect on company value, profibility which was measured with ROA had an effect on company value, company size which was measured with ln(total assets) had an effect on company value, and liquidity which was measured with current ratio had no effect on company value.